2021
DOI: 10.3390/w13243486
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a Calculator for the Environmental and Financial Potential of Drain Water Heat Recovery in Commercial Kitchens

Abstract: Food service providers like restaurants, cafes, or canteens are of economic importance worldwide, but also contribute to environmental impacts through water and energy consumption. Drain water heat recovery from commercial kitchens, using a heat exchanger, has shown large potential to decarbonise hot water use across food services, but is rarely deployed. This work translates previous findings on the technical feasibility and heat recovery potential for commercial kitchens into a publicly available calculator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Buildings mainly use heat exchangers mounted on the outlet of warm drain water [9]. This solution can be used in both residential and industrial facilities [10]. For larger amounts of wastewater, a heat pump application is necessary [11].…”
Section: Introductionmentioning
confidence: 99%
“…Buildings mainly use heat exchangers mounted on the outlet of warm drain water [9]. This solution can be used in both residential and industrial facilities [10]. For larger amounts of wastewater, a heat pump application is necessary [11].…”
Section: Introductionmentioning
confidence: 99%
“…This example illustrates in-depth discipline research and transdisciplinary integration of engineering and environmental science in collaboration with kitchen operators. The research study has demonstrated the potential for DWHR in the hospitality sector, combining the design, development and installation of the DWHR demo site with the environmental science leading to the design and development of the Heat Recovery Toolkit for commercial kitchens (Schestak et al, 2021).…”
Section: Researching Green Process Innovationmentioning
confidence: 99%
“…This technology has significant potential to reduce energy consumption for domestic hot water (DHW) preparation [19], but is often met with reluctance by potential users [20]. It can find application in both residential [21] and commercial buildings [22]. Less conventional solutions are also increasingly being considered.…”
Section: Introductionmentioning
confidence: 99%